Pemberdayaan PKK melalui Implementasi Pertanian Hidroponik di RW. 08 Desa Cipagalo, Kabupaten Bandung Guna Mendukung Ketahanan Pangan - Anwar, Radial; Hadiyoso, Sugondo; Putri, Hasanah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This community service activity aims to implement hydroponic farming in the PKK group of RW 08, Cipagalo Village, Bandung Regency, as an effort to support local food security. Hydroponics is a farming method that does not use soil but instead relies on water enriched with essential nutrients required by plants. This method was chosen due to its efficiency in land and water usage, as well as its ability to produce faster and higher-quality harvests. The training and implementation of hydroponic farming involved the women of the PKK group as the primary participants, with the goal of enhancing their knowledge and skills in modern farming techniques. This activity also aims to empower the local community, especially women, to support family and community food security. In the context of the Sustainable Development Goals (SDGs), this initiative contributes to several objectives, including zero hunger, decent work and economic growth, and sustainable cities and communities..The results of this activity demonstrate that hydroponic farming can be successfully applied in the PKK environment of RW 08, Cipagalo Village. The training participants were able to master basic hydroponic techniques and independently produce fresh vegetables. Additionally, this program successfully raised community awareness about the importance of food security and environmental sustainability